Strategi Optimalisasi Peranan Pendidikan Sekolah dalam Upaya Pencegahan Dini Tindak Pidana Korupsi - Loso .; Ahmad Suharto; Dwi Aryo Fajar (LPPM Universitas Pekalongan, 2015)
abstract Early warning of corruption crime could be done earlier through education. School could make various policy strategy in building anti-corruption attitude for students. This research aimed to create policy strategy for building anti-corruption chacarcter for students. This research used sociological juridic approach and descriptive analitic.From the research result, school could do several steps or strategy in bilding anti-corruption attitude through : 1) integrate the anti-corruption character in lessons or subject; 2) uphold the diciplines of the school rules especially when examination goes on; 3) socialize to the students about the crime of corruption; 4) build the canteen of honesty; 5) show the role model of honest and diciplines attitude to the students; 6) apply the transparent and accountability toward activities inn the school; 7) integrate to the extra curicular in building anti-corruption attitude; 8) publish anti-corruption posters; 9) make anti-corruption education curriculumKeywords: corruption crime, policy strategy, Anti-corruption educatio